A fleeting moment - Heng, Jeth Guan Seng (2018)
A Fleeting Moment is a Final Year Thesis Film about two ex-lovers, entrapped by memories of a decade lost to them, meeting by chance in the town they met. Time seems to have stopped since then, allowing them a chance to pick up where they left off.